PENGARUH PENERAPAN MODEL PEMBELAJARAN CTL DENGAN MEDIA LINGKUNGAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI KOLOID - Tsurayya Zhafirah; Lisa Utami (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
The research was instigated by the low of students learning motivation. It knowing from the questinnaire of learning motivation. The aimed of this research at knowing the Effect of Implementation of Contextual Teaching and Learning Model with environmental media toward students learning motivation on colloid lessson at State Senior High School 3 Pekanbaru. It was experiment research. Simple random sampling was used the technique of collecting the sample. the students of eleventh grade of IPA 1 as experiment group 1 by implementating of contextual teaching and learning with environment media. And the student of eleventh of IPA 3 as experiment group II by implementing of contextual teaching and learning model. The result of analysis showed that everage of student motivation learning at the experiment group 1 was higher than experiment group II was 77.04 > 67.47. both of them were the percentage on high category. The result of anlysis tes by using t-test, t-obseverved was (3.829) > t-table was (1.669). It meant that H0 was rejected and Ha was accepted. It shows that there was effect of implementation of contextual teaching and learning model with enviromental toward students learning motivation on colloid lessson. Keywords : Learning Model, Contextual Teaching and Learning, Environmental Media, Learning Motivation, Colloid